IMPLEMENTATION OF THE SYSTEMATIC CADASTRE IN SECTOR NO. 6 OF GĂNEŞTI COMMUNITY, MUREŞ COUNTY, ROMANIA (PANGEEA, 2026)
The work is part of the systematic cadastre (of the cadastre and land registry program - PNCCF), representing an operation regulated by Order no. 1/2020 for the implementation, verification and reception of systematic cadastre works and the ex officio and free registration of real estate in the land registry, through which the identification of real estate owners is carried out, the measurement of real estate located within cadastral sector no. 6 of the Găneşti Territorial Administrative Unit, the registration of real estate in the land registry and at the same time their representation on cadastral maps and plans free of charge.